Kajian Hukum Penanaman Modal Asing dalam Usaha Perkebunan Kelapa Sawit di Indonesia - Bunga Agnita (Jurnal Ilmu Hukum, Humaniora dan Politik, 2024)
The writing aims to discuss the foreign investment law in the oil palm plantation business activites in Indonesia, particularly after the enactment of UU Ciptaker 2020 and its implementing regulations that have an impact on UU No. 25 Tahun 2007 concerning investment, especially in the context of investment in the oil palm plantation sector. The research objective is to determine the applicable investment regulations for foreign investment activities in the oil palm sector, specifically after the enactment of UU Ciptaker 2020. The researched method used is the normative legal research method with a juridical and descriptive analytical approach. Based on the research results, the conclusion are as follows: (1) every sector is generally open to foreign investment activities, except for sectors determined to be closed and can only be operated by the Central Government and the open sectors referred to are those of a commercial nature, (2) restrictions foreign ownership in oil palm plantation business no longer apply, allowing Foreign Investors to control or own 100% shares in oil palm plantation companies.